Bridging the Worlds: Metaphor in Interdisciplinary Contexts - Revita, Ike; Ferdinal, Ferdinal; Oktavianus, Oktavianus; Asnan, Gusti; Herwandi, Herwandi (Jurnal Arbitrer, 2024)
This conceptual article explores the role of metaphor in navigating and bridging the diverse realms from an interdisciplinary context. Metaphor, as both a linguistic device and a cognitive mechanism, is a powerful tool for transcending disciplinary boundaries, facilitating the exchange of ideas, and fostering innovation in language. This article built the concepts underlying mechanisms through which metaphor enables the synthesis of knowledge from Linguistics, Literature, History, Archeology, and Culture. Furthermore, the article examines the implications of metaphor use in interdisciplinary contexts, including its potential to enhance collaboration, creativity, and problem-solving. This article contributes to a deeper understanding of knowledge integration and synthesis dynamics in today’s increasingly interconnected academic investigations. In linguistics, metaphor is a powerful tool for understanding abstract notions through verbal expression. Metaphor in literature enhances narrative and symbolism by adding layers of meaning and emotion to writings. In history, metaphor is a tool through which people perceive events and narratives, affecting historical discourse and collective memory. In archaeology, metaphor assists the interpretation of material culture and reconstructs the former cultures and their symbolic systems. Metaphors are essential in cultural communication because they shape cultural narratives, identity formation, and social understanding.